No experimental evidence of an adaptive antioxidative response induced by trace metals exposure in feral pigeons - Schmitt, Clarence; Cavaud, Louise; Moullec, Héloïse; Leroux-Coyau, Mathieu; Walch, Laurence; Gasparini, Julien (SPRINGER HEIDELBERG, 2025)
Trace metals produced by anthropogenic activities in particular in urban environments, such as lead and zinc, can induce oxidative damage in exposed individuals. Therefore, trace metals could act as a selective pressure for higher resistance to oxidative damage by favoring individuals able to plastically produce antioxidants once exposed to metal to counterbalance the oxidative damage production. In this study, we experimentally challenge this hypothesis in 69 feral pigeons (Columba livia var. domestica) originating from an urban environment by exposing a subset of them to zinc (n = 18), lead (n = 17) or zinc and lead (n = 16) during 14 weeks to see if exposed individuals showed an increased anti-oxidant production compared to controls (n = 18). Our results reported that zinc exposure induced oxidative stress by increasing oxidative damage but failed to detect a compensatory production of antioxidants in exposed individuals. However, our results report lower oxidative damage for reproducing individuals, which is consistent with an oxidative shielding phenomenon occurring prior to reproduction in males to protect the sperm, and during egg-laying in females to protect offspring. In conclusion, our study does not support an adaptive antioxidative response in individuals exposed to trace metals, but it does partly support the oxidative shielding hypothesis.Keine experimentellen Hinweise f & uuml;r eine adaptive antioxidative Reaktion, die durch Spurenmetallexposition bei Stadttauben ausgel & ouml;st wirdSpurenmetalle wie Blei und Zink, die durch anthropogene Aktivit & auml;ten, insbesondere in st & auml;dtischer Umgebung, entstehen, k & ouml;nnen bei exponierten Individuen oxidative Sch & auml;den hervorrufen. Daher k & ouml;nnten Spurenmetalle als Selektionsdruck f & uuml;r eine h & ouml;here Resistenz gegen oxidative Sch & auml;den wirken, indem sie Individuen beg & uuml;nstigen, die in der Lage sind, nach einer Metallexposition plastisch Antioxidantien zu produzieren, um die Produktion oxidativer Sch & auml;den auszugleichen. In dieser Studie haben wir diese Hypothese bei 69 verwilderten Tauben (Columba livia var. domestica), die aus einer st & auml;dtischen Umgebung stammen, experimentell & uuml;berpr & uuml;ft, indem wir Untergruppen von ihnen 14 Wochen lang Zink (n = 18), Blei (n = 17) oder Zink und Blei (n = 16) ausgesetzt haben, um zu sehen, ob die exponierten Individuen im Vergleich zu Kontrollen (n = 18) eine erh & ouml;hte Produktion von Antioxidantien aufweisen. Unsere Ergebnisse zeigen, dass die Zinkexposition oxidativen Stress durch eine Erh & ouml;hung des oxidativen Schadens induzierte, aber es gelang nicht, eine kompensatorische Produktion von Antioxidantien bei den exponierten Individuen nachzuweisen. Unsere Ergebnisse zeigen jedoch geringeren oxidativen Schaden bei sich fortpflanzenden Individuen, was mit einem oxidativen Abschirmungsph & auml;nomen & uuml;bereinstimmt, das vor der Fortpflanzung bei m & auml;nnlichen Tieren zum Schutz der Spermien und w & auml;hrend der Eiablage bei weiblichen Tieren zum Schutz der Nachkommen auftritt. Zusammenfassend l & auml;sst sich sagen, dass unsere Studie eine adaptive antioxidative Reaktion bei Individuen, die Spurenmetallen ausgesetzt sind, nicht unterst & uuml;tzt, aber sie unterst & uuml;tzt teilweise die Hypothese der oxidativen Abschirmung.